Sonography of Magnetically Controlled Growing Rods: A Quality Initiative in the Creation of a Multidisciplinary Clinic. (November 2020) - Riemann, Monique C.; Bailey, Smita S.; Rubert, Nicholas; Barnes, Craig E.; Karlen, Judson W.
Objective: The MAGEC (Magnetic Expansion Control) rods were introduced to a medical institution in 2015. The rod expansion procedures were initially evaluated with radiographs. The staff undertook a quality initiative to reduce radiation exposure by utilizing sonography. Material and Methods: The radiation dose for a typical visit was measured by examining DICOM imaging data, stored in PACS. Imaging visit time was determined from the difference between times of first radiograph/sonogram before distraction to last radiograph/sonogram after distraction. Results: The 21 patients (8 male, 13 female) were an average age of 11.4 ± 2.82 years (age at implant = 7.5 ± 1.94) when evaluated. The average length of time for a radiographic visit was 40.7 ± 20.7 minutes, whereas a sonography visit was 10.7 ± 3.7 minutes. Radiation dose per study visit prior to the introduction of the MAGEC clinic was 0.42 ± 0.39 mSv. Given an ideal patient schedule, the MAGEC clinic could reduce radiation dose by 1.3 to 2.5 mSv annually, with 95% confidence. Conclusion: This quality improvement study demonstrated a reduction in radiation exposure and imaging time. The added benefits were providing a successful multidisciplinary imaging clinic and creation of a new exam that aligned with the "ultrasound first" initiative.